Effect of the Tea Tree Oil on Growth Performance, Meat Quality, Serum Biochemical Indices, and Antioxidant Capacity in Finishing Pigs - Yang, Tianyu; Feng, Feifei; Zhan, Kang; Ma, Xiaoyu; Jiang, Maocheng; Datsomor, Osmond; Zhu, Xinyu; Huo, Yongjiu; Zhao, Guoqi (Frontiers in Veterinary Science, 2022)
The increased use of antibiotics continues to pose a threat to public health due to the increasing concern of antibiotic residue. Tea tree oil (TTO) is an extract of the Australian plant Melaleuca alternifolia with anti-inflammatory and antioxidant properties. However, there is little information on TTO supplementation on the diet of finishing pigs. Hence, the aim of the present study was to investigate the effect of TTO supplemented diets on serum biochemical indices, meat quality, the mRNA expression of genes related to growth performance and meat quality, and antioxidant capability in finishing pigs. Our results showed that TTO supplementation increased (P < 0.05) the mRNA expression of insulin-like growth factors -I (IGF-I), growth acceleration hormone (GH) and heart fatty acid binding protein (H-FABP), while the mRNA expression of myostatin gene (MSTN) and calpain-1 (CAST) decreased by TTO supplementation, compared with control group. In addition, TTO supplementation increased (P < 0.05) serum alkaline phosphatase (ALP), immunoglobulin G (IgG), and IgM levels but decreased (P < 0.05) serum aspartate transaminase (AST) concentration, relative to control group. In addition, we found that the live weight, and intramuscular fat enhanced (P < 0.05) significantly, and muscle pH 24 min value, cooking loss, and shear force decreased (P < 0.05) dramatically in TTO group. The TTO supplementation increased (P < 0.05) C18:2n6t concentration and decreased (P < 0.05) C12:0 and C16:0 concentration, relative to control group. Dietary supplementation with TTO decreased (P < 0.05) malondialdehyde (MDA) and increased (P < 0.05) glutathione peroxidase (GSH-Px) activity in serum. These results indicated that TTO supplementation could improve immunity and antioxidant, carcass traits, nutritional value of pork, and antioxidant capacity of finishing pigs. Therefore, TTO has potential positive effects as a feed additive in pigs industry.